USING YOUTUBE VIDEO RESOURCES TO FORM A TOLERANT ATTITUDE TOWARDS CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Iryna Subashkevych; Vira Korniat; Viktoriya Loboda (Borys Grinchenko Kyiv Metropolitan University, 2020)
he article deals with the problem of professional training of specialists majoring in Pedagogics at Ivan Franko National University of Lviv, Ukraine, for working with children with special educational needs under conditions of inclusive education, which is useful not only for children with special educational needs, but also for their peers and parents, since such interaction contributes to the development of empathy, tolerance, an objective assessment of one's own capabilities, the formation of a realistic mind-set. Describes the innovative experience of introducing students of the Faculty of Pedagogical Education to study the course «Fundamentals of Media Literacy», which will allow them to critically analyze media messages, consciously perceive and analyze information, separate reality from its virtual simulation, comprehend power relations, myths and types of control they cultivate. The reasons for such actions, as well as to understand the structural elements that affect the information, etc. The emphasis is placed on the need to improve the educational process at the university in order to train competent staff ready to work with children with SEN. A comparative analysis of course units is presented, according to the curricula in different majors: «Pre-school Education», «Primary education», «Social Pedagogy» and «Social Work». A series of practical media products, namely the use of YouTube video resource, is proposed to form tolerant attitude of students majoring in pedagogies towards children with special educational needs. A number of cartoons from the YouTube video resource have been selected, which can be used in various forms of work with parents and students to get acquainted with the peculiarities of this category of children and reduce distrust. There is a video selection of cartoons, links to sources for viewing by children and fathers in order to develop a tolerant attitude towards children with special educational needs and their problems. The work will promote inclusion in the educational environment, help free children with special educational needs from social isolation, form their healthy interaction with «normal» children, and develop a positive, patient, loyal attitude on the part of others.